An investigation on the effects of emotional intelligence in development of brand equity - Hosseinali Aziziha; Ashkan Faraji; Ali Khodsetan; Reza Tahermanesh; Seyed Shahab Mousavi; Elham Agha Alikhani (Management Science Letters)
This paper presents an investigation on the effects of various components of emotional intelligence including self-awareness, emotional management, sympathy, social skills and self- motivation on building brand equity in telecommunication industry. The proposed study of this paper uses two questionnaires, one for measuring emotional intelligence and the other for measuring brand equity. The study was performed among 384 people who had used telecommunication industry services in city of Tehran, Iran. Using Spearman correlation test, as well as structural equation modeling, the study has confirmed the positive effects of four emotional components, including self-awareness, emotional management, social skills and self-motivation influence on building brand equity in telecommunication industry.